USE OF OVSYNCH ± POST INSEMINATION PROGESTERONE (CIDR) FOR SUCCESSFUL CONCEPTION IN REPEAT BREEDER BUFFALO - RAJA, S; VIJAYARAJAN, A; PRABAHARAN, V; JAYAGANTHAN, P; SIVAKUMAR, A; JAYAGANTHAN, P; SIVAKUMAR, A; SATHESH KUMAR, S (The Indian Journal of Animal Reproduction, 2016)
Sixteen repeat breeder buffalo were subjected to timed-insemination protocol (ovsynch) with or withoutsupplementation of progesterone from day 5 to 18 post-insemination. The conception rate in ovsynch group was37.5% and in ovsynch plus progesterone group was 75%. Thus, timed-insemination with or without progesterone cansuccessfully used to conceive repeat breeder buffalo
Keywords: Buffalo; CIDR; Conception; Ovsynch; Repeat breeder